The Growth of Alocasia macrorrhiza Variegata Roots on Murashige and Skoog medium supplemented 6-Benzyl Amino Purine (BAP) and Kinetin - Arif Yachya; Nisa Novi Afina; Vivin Andriani; Siti Wardania; Rosa Adelia Aryaning Fidya Putri; Nada Tika Sari; Eka Nur Indah Sari Sartono Putri (Biota, 2023)
The sente variegata plant (Alocasia macrorrhiza variegata) is a species of ornamental taro. The unique leaf color of sente variegata, which is a combination of white and green, attracts ornamental plant lovers for hunting or collecting. There has been no cultivation effort from the ornamental plant suppliers and traders for multiplication purposes until now. Sente variegata is obtained directly from the forest. This activity can cause extinction. Micropropagation efforts using plant tissue culture techniques are needed for commercial and sustainability issues. This study aimed to determine the effect of 6-Benzyl Amino Purine (BAP) and kinetin on the root formation and growth as one step in the shoot multiplication of sente variegata bulb explants. Variations in BAP and kinetin concentrations used separately in this study were 0, 2, 5, and 10 mg. L-1. The results showed that the application of BAP and Kinetin significantly affected the root growth of sente Variegata. Finally, kinetin 10 mg L-1 is the concentration and type of cytokinins recommended for the formation and root growth of sente variegate.